2020
DOI: 10.17221/87/2020-pps
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of thrips from Slovakia with emphasis on economic species

Abstract: Almost sixty years after the first published plea for more systematic research on thrips in Slovakia, the checklist undisputedly requires an appropriate revision with a special emphasis on the economic consequences of climate change and biological commodity trade globalisation synergic effects, followed by the dynamic and significant changes in the native biodiversity due to alien species introduction. The updated checklist contains 189 species  ecorded from the area of Slovakia, from three families: Aeolothri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, it has been reported that T. flavus transmits the tomato spotted wilt virus that infects watermelon (TSWV-W) [1,11]. T. flavus has well-developed mechanisms for its successful dispersion and may have the potential to cause large infestations [12]. T. flavus has been increasingly recognized as one of the main pests on soybean from the flowering stage to early stage of podding in Northeast China [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that T. flavus transmits the tomato spotted wilt virus that infects watermelon (TSWV-W) [1,11]. T. flavus has well-developed mechanisms for its successful dispersion and may have the potential to cause large infestations [12]. T. flavus has been increasingly recognized as one of the main pests on soybean from the flowering stage to early stage of podding in Northeast China [13].…”
Section: Introductionmentioning
confidence: 99%
“…Matsum. et Nakai) in India [ 4 , 5 ], which is highly invasive to other regions since it has well-developed dispersion mechanisms [ 6 ]. T. flavus has been increasingly recognized as a dominant pest of Compositae (Asteraceae), Leguminosae (Fabaceae), and other plant families during the flowering stage in north China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, T. flavus is the main vector of the tomato spotted wilt virus of watermelon (Boonham et al, 2002; Jones, 2005; Mound, 1996; Singh & Krishnareddy, 1995). T. flavus is highly likely to invade other regions, since it has well‐developed mechanisms of dispersion (Zvaríková et al, 2020). In recent years, T. flavus has increasingly become a major phytophagous pest on soybean [ Glycine max (Linn.)…”
Section: Introductionmentioning
confidence: 99%